CD4 and CD8 monoclonal antibody therapy in canine renal allografts. - Watson, C; Cobbold, S; Davies, H; Rebello, P; Waldmann, H; Calne, R; Metcalfe, S (1994)
Therapy with CD4 and CD8 monoclonal antibodies was evaluated in dogs which received double-haplotype MHC-mismatched renal allografts. Neither CD4 nor CD8 monoclonal antibodies given alone prolonged allografts survival (creatinine > or = 300 micromol/l) beyond 7 days. However, combined therapy with CD4 and CD8 antibodies given up to day 10 did prolong allograft survival to a median of 14 days. A longer (21 day) course of CD4 and CD8 antibodies did not extend allograft survival further. The effect of prolonged antibody therapy was restricted by the occurrence of both an antiglobulin response and an anaphylactoid reaction to the monoclonal antibody preparation. When the CD4 and CD8 antibodies were combined with a pan-T-cell-depleting Thy-1 antibody, the survival of double-haplotype mismatched allografts was further prolonged (median 16 days). The median survival of single-haplotype mismatched renal allografts on this triple therapy was 21 days, with one surviving to day 36.